Feasibility of triacylglycerol production for biodiesel, utilizing Rhodococcus opacus as a biocatalyst and fishery waste as feedstock. (April 2016) - Palmer, Jacob D.; Brigham, Christopher J.
Abstract: Triacylglycerols (TAGs) can be produced via bacterial fermentation by the oleaginous Gram-positive microorganism Rhodococcus opacus strain PD630 in regulated, nutrient-deprived conditions with sufficient carbon supply. Microbially produced TAGs may be further refined via transesterification into biodiesel and glycerol, with 3 mole of biodiesel and 1 mole of glycerol produced from every 1 mole of TAG by chemical conversion. Large-scale industrial production of biodiesel has been conducted for over a decade, yet microbially derived biodiesel has been, up to this point, absent from the biodiesel market. The use of a novel feedstock, chitin, from New England fishery waste may present a viable, cost-effective, unexplored carbon feedstock source for local biodiesel development. Availability and implementation of chitin as a feedstock, along with analysis of potential fuel characteristics, yield promising results for future industrial development of biodiesel production from R. opacus PD630 TAGs in regional locations with large lobster, shrimp, and crab harvesting operations around the world. With declining resources of fossil fuels and increased societal awareness of carbon emissions and climate change, an analytical review of this nature is critically relevant.